Survival and risk of breast cancer recurrence after breast reconstruction with deep inferior epigastric perforator flap. Issue 11 (12th July 2018) - Svee, A.; Mani, M.; Sandquist, K.; Audolfsson, T.; Folkvaljon, Y.; Isern, A. E.; Ringberg, A.; Manjer, J.; Falk‐Delgado, A.; Wärnberg, F.
Abstract : Background: Women who undergo autologous breast reconstruction have been reported to have an increased risk of breast cancer recurrence compared with those who have mastectomy alone. It has been suggested that more extensive surgery possibly activates dormant micrometastases. The aim of this study was to evaluate whether delayed unilateral deep inferior epigastric perforator (DIEP) flap reconstruction after mastectomy increases the risk of breast cancer recurrence or affects mortality among women previously treated for breast cancer. Methods: This was a matched retrospective cohort study including women with a previous unilateral invasive breast cancer who received a delayed DIEP flap breast reconstruction and a control cohort of individually matched women with unilateral breast cancer who underwent mastectomy but no autologous breast reconstruction. Matching criteria comprised: year of diagnosis (+/–3 years), age at diagnosis (+/–5 years), type of cancer and demographic region. The primary endpoints were local recurrence or distant metastasis, and overall mortality was a secondary endpoint. Absolute risk of recurrent disease and mortality was analysed, and relative risks were estimated using Cox proportional hazards analysis. Results: There were 225 women in the DIEP cohort and 450 in the no‐DIEP cohort. The median follow‐up time was 125 months. There was no difference in absolute risk of recurrence between the cohorts. The hazard ratio for breast cancer recurrence in DIEP versus no‐DIEP cohorts was 0·76 (95 per cent c.i. 0·47 to 1·21). Conclusion: There is no increased risk in breast cancer recurrence after delayed DIEP flap reconstruction compared with mastectomy alone. Abstract : As above